Drug-induced Neuropsychiatric Adverse Events Using Post-Marketing Surveillance - Wakabayashi, Tomohito; Nakatsuji, Takahiro; Kambara, Hiroko; Niinomi, Iku; Oyama, Saki; Inada, Ayaka; Ueno, Sayaka; Uchida, Mayako; Iwanaga, Kazunori; Iida, Tatsuya; Hosohata, Keiko (Current Reviews in Clinical and Experimental Pharmacology, 2022)
Background: Several studies reported that abnormal behavior was noted in pediatric patients receiving several drugs, including neuraminidase inhibitors (NIs). However, the information on drugs associated with abnormal behavior in a real-world setting remains limited. The purpose of this study was to clarify the drugs associated with abnormal behavior using a spontaneous reporting system database. Methods: We performed a retrospective pharmacovigilance disproportionality analysis using the Japanese Adverse Drug Event Report database. Adverse event reports submitted to the Pharmaceuticals and Medical Devices Agency were analyzed, and the reporting odds ratio at 95% confidence interval were calculated. Results: A total of 1,144 reports of abnormal behavior were identified. The signals were detected through the association of 4 neuraminidase inhibitors (oseltamivir, zanamivir, laninamivir, and peramivir) with the abnormal behaviour. These signals were stronger for oseltamivir than other neuraminidase inhibitors. The signals were also detected for acetaminophen and montelukast. Conclusion: Our results should be able to raise physicians’ awareness of drugs associated with abnormal behavior, but further investigation of these medications is warranted.
Keywords: Japanese Adverse Drug Event Report (JADER) database